PENGARUH DESKRIPSI KERJA DAN KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN PT. BPR WAHANA SENTRA ARTHA KADIPATEN - H. Masduki (MAKSI, 2015)
This study was conducted to identify: how to influence job descriptions on jobperformance, how the influence of compensation on employee performance, how to influencejob description and compensation on employee performance PT. BPR Wahana Sentra ArthaDuchy simultaneously.Methods This study uses descriptive methods and verification with retrieval of datausing questionnaires from total population using census sampling technique.The results stated that the job description and compensation have a strongrelationship to the job performance of employees of PT. BPR Wahana Sentra Artha. Jobdescription affect employee performance and signifikan. Compensation positively affectemployees' performance is positive and significant. Simultaneously, job descriptions,employee performance affects positively and significantly.Keywords: job description, compensation, and job performance*) Penulis